Integrasi Metode Fitoremidiasi dan Filtrasi pada reaktor Portabel untuk Pengolahan Air Limbah Gelondongan Mengandung Merkuri di Sekitar Danau Lebo, Sumbawa Barat - Abdul Rahman; Puryadi; Andi Maria Ulfa (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to design and test the effectiveness of a portable reactor based on filtration and phytoremediation in reducing mercury levels in gold processing wastewater. The study was conducted experimentally using a portable reactor with a water lettuce (Pistia stratiotes) phytoremediation unit and a filtration unit made of biofoam, zeolite rock, and activated carbon. Testing was carried out on contact time variations of 0–120 minutes and repeated use up to 15 times, with mercury level analysis using AAS. The results showed that the reactor was able to reduce mercury levels from 0.7095 mg/L to 0.0040–0.0039 mg/L at a contact time of 90–120 minutes with an efficiency of up to 99.45%, thus meeting the applicable quality standards. The minimum contact time for the reactor to work optimally was 90 minutes. In repeated use, the highest effectiveness occurs in the initial stage, then decreases due to saturation of the filtration media. This portable reactor is effective and has the potential to be applied directly at PETI sites as a practical alternative technology for mercury waste treatment.